Hedendaagse schilderkunst in België. - Callewaert, Marc; Michiels, Ivo; Walravens, Jan (De Kunst-meridiaan Vereniging Taptoe, 1959)
Alechinsky, Pierre ; Van Anderlecht, Englebert ; Bertrand, Gaston ; Bogaert, André ; Bonnet, Anne ; Van Breedam, Camiel ; Burssens, Jan ; Claus, Hugo ; Cox, Jan ; Delahaut, Jo ; Dorchy, Henri ; Van Hoeydonck, Paul ; Lacomblez, Jacques ; Landuyt, Octave ; Leblanc, Walter ; de Leeuw, Bert ; Van Lint, Louis ; Mara, Pol ; Marstboom, Antoon ; Mendelson, Marc ; Milo, Jean ; Mortier, Antoine ; Peire, Luc ; Raveel, Roger ; Van Severen, Dan ; Slabbinck, Rik ; Vaerten, Jan ; Vandenbranden, Guy ; Vandercam, Serge ; Verstockt, Mark ; Wyckaert, Maurice
De kunst-meridiaan zesde jaargang, nr. 1 en 2
Nederlands
boek
Keywords: België